Telemedicine Foot and Ankle Visits in the COVID-19 Era. Issue 1 (19th February 2021) - Labib, Sameh A.; Goel, Rahul; Manz, Wesley; Bariteau, Jason
Background: The COVID-19 pandemic created a difficult environment to provide musculoskeletal care to patients with foot and ankle pathology given the limitations placed on in-office visits. Telemedicine offered a unique avenue to reach these patients; however, the efficacy of telemedicine visits in patients with foot and ankle pathology is not well studied. We propose a telemedicine protocol that has allowed us to effectively see and treat patients with foot and ankle pathology. Methods: A 12-step standardized telemedicine protocol was created within the Foot and Ankle division that was used for seeing patients through telemedicine. Also included in this is previsit preparation and follow-up recommendations. Press Ganey surveys were retrospectively reviewed to understand patient experience with telemedicine. Results: 85.2% of patients surveyed responded with scores indicating excellent care. When comparing patients who were seen in-office and through telemedicine, 89.2% and 83.4% responded with scores indicating excellent care, respectively ( P = .37). Conclusion: Telemedicine offers an effective and convenient way to provide excellent musculoskeletal care to patients affected with foot and ankle pathology. This is the first study that evaluated a comprehensive protocol for telemedicine encounters and can be used to implement telemedicine by others using this approach. Level of Evidence: Level V, expert opinion.